Association of sleep quality and psychological aspects with reports of bruxism and TMD in Brazilian dentists during the COVID-19 pandemic - Karen Oliveira Peixoto; Camila Maria Bastos Machado de Resende; Erika Oliveira de Almeida; Camila Megale Almeida-Leite; Paulo César Rodrigues Conti; Gustavo Augusto Seabra Barbosa; Juliana Stuginski Barbosa (University of São Paulo, 2021)
Abstract Dentists are exposed to contamination by SARS-CoV-2 due to dental interventions, leading to a state of alert and potential risk of negative impact in mental health and sleep quality, associated with Temporomandibular Disorder (TMD) and bruxism. Objective: to evaluate the psychosocial status, sleep quality, symptoms of TMD, and bruxism in Brazilian dentists (DSs) during the COVID-19 pandemic. Methodology: The sample (n=641 DSs) was divided into three groups (quarantined DSs; DSs in outpatient care; and frontline professionals), which answered an electronic form containing the TMD Pain Screening Questionnaire (Diagnostic Criteria for Temporomandibular Disorders - DC/TMD), the Pittsburgh Sleep Quality Index (PSQI), the Depression, Anxiety and Stress Scale (DASS-21), and the sleep and awake bruxism questionnaire. ANOVA test and Mann Whitney post-test were used, with Bonferroni adjustment (p<0.016) and a 95% confidence level. Results: Probable TMD was found in 24.3% (n=156) of the participants, while possible sleep and awake bruxism were diagnosed in 58% (n=372) and 53.8% (n=345) of them, respectively. Among all variables evaluated, only symptoms of depression were significantly greater in the quarantined DSs group when compared to those who were working at the clinical care (p=0.002). Working DSs were significantly less likely (OR=0.630, p=0.001) to have depressive symptoms. Those who were not worried or less worried about the pandemic were less likely to experience stress (OR=0.360), anxiety (OR=0.255), and poor sleep quality (OR=0.256). Sleep had a strong positive and moderate correlation with psychological factors on frontline workers and DSs in outpatient care, respectively. Conclusion: The results suggest confinement may have a more negative impact on the life of DSs than the act of being actively working. The concern about Covid-19 and poor sleep quality was significantly prevalent and may negatively affect the quality of life of DSs. Thus, further research on the topic is needed.